2023
DOI: 10.3390/nu15040987
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Activity of Fecal Enzymes and Concentration of SCFA in Healthy and Overweight Children

Abstract: In modern societies obesity has become a serious issue which must be urgently addressed. The health implications of neglected obesity are substantial, as not only does it affect individuals’ everyday lives, but it also leads to significantly increased mortality due to the development of several disorders such as type-2 diabetes, cardiovascular diseases, cancers, and depression. The objective of this research was to investigate the alterations in selected health markers caused by overweight and obesity in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In light of the concerning rise in childhood obesity, Śli żewska and colleagues demonstrated differences in the activity of fecal enzymes and profiles of fatty acids (short-chain fatty acids, branchedchain fatty acids) between obese children and those of normal weight. These results confirm the adverse metabolic effects associated with obesity, which can lead to the development of chronic diseases [6].…”
supporting
confidence: 76%
“…In light of the concerning rise in childhood obesity, Śli żewska and colleagues demonstrated differences in the activity of fecal enzymes and profiles of fatty acids (short-chain fatty acids, branchedchain fatty acids) between obese children and those of normal weight. These results confirm the adverse metabolic effects associated with obesity, which can lead to the development of chronic diseases [6].…”
supporting
confidence: 76%
“…The same effect was observed for the activity of α- and β-glucosidase and α- and β-galactosidase. These enzymes assist in the hydrolysis of indigestible oligosaccharides derived from the diet and, thus, indirectly affect the supply of substrate for the synthesis of bacterial SCFAs in the intestine [ 43 ]. Moreover, low galactosidase activity may increase colonic fermentation and gas production, which is undesirable, especially in people with irritable bowel syndrome [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the rats under the M dietary treatment, considerably lower concentrations of CA and DCA were found in the cecum. These bile acids had a significant inhibitory effect on the growth of potentially prebiotic bacterial strains, e.g., Lactobacillus casei , Clostridium butyricum , and Bacillus mesentericus [ 2 ], which are SCFA-producing strains and exhibit increased enzymatic activity for the hydrolysis of oligosaccharides [ 43 ]. Therefore, the reduction in DCA and CA through switching from a high-fat diet to a standard diet may partially explain the increased activity of β-glucosidase, α-galactosidase, and β-xylosidase in the cecum.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined SCFA levels in children with obesity, however, within the last 5 years, two studies showed increased fecal SCFA concentrations ( 118 , 119 ), while one study showed fecal SCFAs were reduced ( 120 ) in children with obesity. The differences in study results may be due to study design and inclusion criteria, as Wei et al and Gyarmati et al excluded volunteers who had received antibiotic, prebiotic, or probiotic treatments within the last 3 months before the studies, while the study by Slizewska et al did not ( 118 120 ).…”
Section: Interplay Of Obesity the Meddiet And Gut-derived Metabolitesmentioning
confidence: 99%